PENGEMBANGAN KARTU UNO SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA DIKAITKAN DENGAN PERMAINAN TRADISIONAL - Kurniati, Ratnah; Sugiarto, Sigit; Andi Mattoliang, Lisnasari; Sairlona, Stelamaris (Universitas Insan Budi Utomo, 2025)
This study aims to develop Uno cards as one of the mathematics learning media associated with the traditional game of papanukit. The method used by the researcher is Research and Development (R&D) with a 4-D development model without dissemination. So that the stages are only limited to the define, design and develop stages. The prototype that was developed then went through the feasibility test stage with validity, trial and product evaluation to produce a revised prototype based on expert input and limited trials on children aged 6-12 years in Wakarleli village, Southwest Maluku Regency. During the study, there were several findings, namely during the product trial, there were several children who helped their friends to answer questions so that it was felt necessary to add rules by giving sanctions to each child who gave an answer. The number cards on the Uno card are only limited to positive numbers, while integers include positive and negative numbers. In this trial, the division operation was the operation that children disliked the most. This is because the division ability of children in Wakarleli village is still very lacking. So, to overcome this problem, the researcher conducted a development with Uno Cards as a Mathematics Learning Media associated with traditional games.